Hak-Hak Perempuan dalam Cerai Gugat - Muhammad Tsaqib Idary; Rhamdani Wahyu Sururie; Idzam Fautanu (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Even though many legal instruments have been created to ensure that the rights of women and children are fulfilled, in the field there is still a lot of neglect of the rights of women and children. The Religious Courts through the formulation of the Supreme Court of Religion chamber of the Republic of Indonesia have created many guidelines for Judges in examining cases and ensuring that the rights of wives and children are fulfilled.based on SEMA No. 1 of 2017, SEMA No. 3 of 2018, SEMA No. 2 of 2019, as well as SEMA No. 5 of 2021 which extends further to the husband's belongings which can be submitted for marital confiscation to ensure that the wife and children are provided for. The type of research that the author uses is norative empirical through library research and experience in trials, with a research approach used as a judicial case study. The conclusion of this article is that the fulfillment of women's rights during a divorce has been carried out in the court process, there is a need for socialization and legal assistance to women so that the fulfillment of their rights after a divorce can be carried out well.